Construção da paisagem aracajuana: modernidade e suas redes marítimas em Sergipe - Silva, Felipe Neves da (2017)
This work deals with the emergence of the city of Aracaju as a modern landscape, aiming, at one time, to deal with multitemporal contingencies that enabled this emergency, without losing sight of its spatiality. The objective is to analyse the material characteristics of the Aracaju city landscape. To do so, we start with na archaeological approach of the landscape in relation with subjects such as history, anthropology, geography and architecture. The materiality, as a support of time, and its implantation, as a testimony in space, are the vestiges of the construction of Aracaju that we aim to emphasize. The temporality of capitalism will be contemplated by an archaeological approach, however, without compromising with an archeology of capitalism in order to avoid historical anachronism. Spatiality will be approached trying to balance the advantages and limitations of a systemic approach in consideration of the spatial characteristics of capitalism present in the conformation of the city. Attention will be given to navigation aiming to restore the "aquatic designs" as a condition of an historical transformation to the nineteenth century. Together with the environmental peculiarities and the space built, this activity brought a concrete dimension of the relations continuum that we understand by landscape.